Transformasi Gelombang Reguler Akibat Pemecah Gelombang Tiang Pancang Dua Baris Selang-Seling - Suprijo, Totok; Napitupulu, Gandhi; Ginting, Juventus W.R.; Simanjuntak, Eduardo M.; Abdullah, Faizal A.R.; Khadami, Faruq (JURNAL TEKNIK HIDRAULIK, 2024)
Hydraulic experiments in a two-dimensional physical laboratory were conducted to evaluate the performance of pile breakwaters in reducing wave energy. The piles on the breakwater were arranged in a staggered pattern in two rows. A total of seventy-two simulation scenarios were run based on variations in the incoming wave height and period, and the spacing between the piles, using a 1:10 model scale. The data from the hydraulic tests were then processed using a spectral method that could separate the energy spectra of reflected and transmitted waves. These changes result in reflected and transmitted waves. The laboratory test data were used to estimate the values of the transmission coefficient and reflection coefficient. Both coefficients were then used to validate semi-empirical formulas for the two coefficients. The semi-empirical formulas for the two coefficients were developed based on a model for estimating the spatial porosity of pile breakwaters. The porosity estimation model takes into account the dimensions of the piles and the dimensional components of the breakwater, including the arrangement, number of rows, and spacing between the piles. The validation results of the semi-empirical formulas with the laboratory test data showed a coefficient of determination of 0.917 and a root mean square of 0.077. The staggered arrangement improves the effectiveness of the breakwater in reducing the transmission wave height. The developed semi-empirical model can be used to design the pile dimensions to achieve optimal reflected and transmitted wave heights for coastal protection. Keywords:  pile breakwater, coastal protection, hydraulic experiment, physical wave simulation, wave transmission new formula